State‐selective cross sections from ring polymer molecular dynamics. Issue 3 (12th September 2020) - Marjollet, Adrien; Welsch, Ralph
Abstract: Understanding the influence of different forms of energy (eg, translational, vibrational, rotational) on chemical reactions is a key goal and great challenge in physical chemistry. Very recently, we proposed a new approach to obtain state‐selective cross sections that approximately include quantum effects such as zero‐point energy and tunneling. The method is a combination of the widely used quasiclassical trajectory approach (QCT) and the ring polymer molecular dynamics method and thus is numerically very efficient and easily employed. Here, we present a detailed description of the method and exhaustive tests of its accuracy and applicability. The robustness of the approach is tested, as well as the convergence with the number of beads. The approach is then applied to several prototypical X + H2 ( ν = 0, 1), X = Mu, H, D, F, Cl reactions over a wide range of collision energies. Good agreement with rigorous quantum dynamics simulations is found for most cases. Encouraging improvement over QCT results is found for particular cases, while only a small increase in numerical cost is required. Abstract : Detailed knowledge of gas‐phase and chemisorption reactions for specific initial states of the reaction partners is of prime importance to understand and possibly control catalysis, combustion and atmospheric processes. However, detailed studies of reaction dynamics through rigorous quantum dynamical simulations are computationally infeasible for most polyatomic reactions. The presented approach calculates approximate quantum state‐selective reactive cross sections efficiently employing an extension of the ring polymer molecular dynamics approach.